Theory of value : an axiomatic analysis of economic equilibrium - Debreu, Gerard (New Haven : Yale University Press, 1959)
The two central problems of the theory that this monograph presents are (1) the explanation of the prices of commodities resulting from the interaction of the agents of a private ownership economy through markets, (2) the explanation of the role of prices in an optimal state of an economy. The analysis is therefore organized around the concept of a price system or, more generally, of a value function defined on the commodity space.
Includes index.
Includes bibliographical references: p. 103-107.
rpm 30/08/2017
Loans
Keywords: Prices; Value; Equilibrium--Economics.